PENGEMBANGAN MEDIA PONDASI UNTUK KEMAMPUAN PROBLEM SOLVING ANAK KELOMPOK B DI TKM NU 12 AZ- ZAHRA PANDANSARILOR JABUNG KABUPATEN MALANG - Novita Anggraini; Ayu Asmah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2021)
This research is motivated by the problem solving abilities of group B children at TKM NU 12 Az-Zahra Pandansarilor Jabung Malang Regency, whose teaching and learning activities are still dominated by the use of learning media in magazines, notebooks and blackboards. So we need media that can stimulate this ability, therefore a learning media is developed which is named pondok cerdas inspirasi (PONDASI). The purpose of this development research is develop an appropriate PONDASI media for the problem solving abilities of group B children at TKM NU 12 Az-Zahra Pandansarilor Jabung, Malang Regency. The development model used in this study is R&D. Data collection techniques using observation, interviews, questionnaires and documentation. Based on the results of the research that has been done, this research produce a PONDASI media with the results of the validation of media experts get a percentage of 95% and material experts 97%. The results of the trial of PONDASI ​​media activities on children obtained 82% results for 8 students and the operational field trials obtained 90% results for 15 students, all of which were categorized as